O mal-estar docente e os limites da experiência no tempo presente: uma leitura frankfurtiana - Manfré, Ademir Henrique [UNESP] (2014)
This research aims at discussing the topic of the instructor’s inquietude and its relations to the formative activity. From a theoretical approach, this research is part of the Graduation Program in Education of FCT/UNESP/Campus of Presidente Prudente/SP, more specifically of the research line on “Formative process, differences and values”. To investigate our topic we assume the assumption that the instructor’s inquietude is due to the process of expropriation of the experience in nowadays. From this, we investigate what is the instructor’s inquietude so that clarifying its meaning. One of the intentions of this research was to think about the contradictions produced by Modernity in relation to its proposal for cultural formation (Bildung). Initially, we make some considerations in respect of the implication of the educational debate on instructor’s inquietude to motivate the reflection about the poorness of experience in nowadays. In a second moment, we discuss the main Freudian thesis, and of others contemporary experts, about the “Civilizations and its Discontents” as an inherent process to the constitution of subjectivities. Finally, our central worry in this work was to think about the challenges posed in nowadays to the achievement of an education based in a formative experience. In this context, we reflected about the importance of conceive the paths for a compromised education with the formation of autonomous individuals, which are able to seek for its own identity, giving a (new) meaning to the perception of reality via its experience. In summary, we saw in the Critical Theory a philosophical-theoretical referential that contemplates the possibility for the development (in different basis) of an analysis of the social process in which is inserted the school education in nowadays, as well its relations to the productions of the instructor’s inquietude.